Pengaruh Pengetahuan Etika Profesi Akuntan Terhadap Persepsi Mahasiswa Akuntansi Mengenai Creative Accounting - Bonifasius H. Tambunan; Astria G. A. Silitonga (Jurnal Riset Akuntansi dan Bisnis, 2020)
The purpose of this study effect of professional ethical knowledge of accountants on accounting students' perceptions of creative accounting among students at the University of HKBP Nommensen Medan. This research is causality. The population in this study were active students of S1 Accounting Study Program, Faculty of Economics, University of HKBP Nommensen Medan who had taken Business and Professional Ethics courses. The sampling technique was purposive sampling technique, namely taking samples with certain criteria, in order to obtain a total of 150 people. The research method used a survey method with a questionnaire. The approach used is quantitative by processing the data obtained from the questionnaire after first being transformed into numeric data using a Likert scale. The data were processed using SPSS 23.0 software. The analysis used is a simple linear analysis. The research instrument test consisted of validity and reliability tests. The classical assumption test consists of normality test, heteroscedasticity test and multicollinearity test. Hypothesis testing consists of t test (partial test) and determinant coefficient test (R2).